India-Nepal Relations: Prisms That Go Beyond Liberal and Realist Theories (International Journal of Innovative Research in Engineering & Management, 2022)
The Nepal-India relationship has  historical, social, political, and cultural facets that are  multidimensional. Open borders and deeply rooted people to-people contacts of kinship and culture distinguish the  unique friendship and cooperation between the two  nations. Based on secondary data, the purpose of this  article is to discuss the major changes in Indo-Nepal  relations following an understanding of 12 points. EPG  was established with four members from each of Nepal's  and India's governments in order to examine previous  agreements and treaties. In a similar vein, India and Nepal  exchanged high-level visits. In 2015, Nepal adopted a new  constitution and published it. However, India unilaterally  imposed a blockade because it was dissatisfied with some  of its contents. Later, relations between Nepal and India  normalized, but Nepal and India still disagree about the  Limpiyadhura-Lipulekh border. What has become of the  relationships based on past ties? This is the most pressing  issue. This paper examines the past and present of India's  relations with Nepal.
Keywords: Bilateral Relation; Blockade; High Level Visits; Promulgation